PENGEMBANGAN KOMIK SEBAGAI MEDIA BELAJAR BIOLOGI MATERI SISTEM RESPIRASI KELAS XI MAN 1 METRO - Ajeng Ayu Srigati; Handoko Santoso; Agil Lepiyanto (EDUBIOLOCK, 2021)
The learning process works because there is interaction and communication between individuals and their environment. Learning can be done alone or with the help of others like parents and teachers, and can also be done with the help of the media. The learning process that takes place in schools today has used a lot of media books that are more varied. Based on interviews conducted with Grade XI teachers of MAN 1 Metro, regarding the learning media used. Grade XI teachers conveyed that the problem in learning in the class is that there are still students who have low interest in reading so there are still students who score below the minimum completeness criteria (KKM) which is 76. The problems found in the MAN 1 Metro school are a lack of student interest in reading and low learning motivation. Media supporting books used in the learning process are also still not attracting students' interest in reading. Then it can be formulated the purpose of development is to produce products in the form of comics as a medium of learning biology on the class XI MAN 1 Metro respiration system material that is feasible to use and can increase student motivation and motivation. The development of comics with this respiration system material is expected to be able to support learning motivation and increase students' memory of the respiration system material. In addition, comics can also be used as learning media that can support and facilitate teachers in delivering respiration system material in the teaching and learning process. The method used to develop comics is the Research and Development (R&D) method The development model used is the 4-D model, there are four stages namely Define, Design, Develop, and Disseminate. The research data was obtained from the results of expert validation and small-group trials. Based on the data collection, the results obtained in the expert material validation obtained a percentage value of 98% with the criteria "Very Good". The validation of learning media experts obtained a percentage value of 94% with the criteria of "Very Good". The validation of comic media experts obtained a percentage value of 96% with the criteria of "Very Good". In small group trials, the percentage value was 84.8%. With "Good" criteria. Based on these criteria stated that the product developed is suitable for use in the field.